Antioxidant Activity Evaluation of Carrot (Daucus carota L.) Extract-Enriched Lip Balm: A Natural Approach for Lip Protection - Hilmia Lukman; Vivi Shofia; Salsabila, Shinta Nova; Maysaroh, Titis (Indonesian Journal of Science and Pharmacy, 2024)
Lips are a part of the body that is vulnerable to free radicals and UV radiation, thus requiring special protection. One effort to protect the lips is through the use of lip balm containing antioxidants. However, synthetic antioxidants in cosmetics can pose health risks, necessitating natural alternatives. This study aims to develop and evaluate lip balm based on carrot extract (Daucus carota L.) as a source of natural antioxidants. The methods used include carrot extraction using the reflux method with 96% ethanol, lip balm formulation with varying concentrations of extract (10%, 15%, and 20%), and antioxidant activity testing using the DPPH method with UV-Vis spectrophotometry. The results showed that lip balm containing carrot extract exhibited good physical characteristics, including homogeneity, color variation depending on the extract concentration, and pH within the suitable range for lip cosmetics (4.5–6.5). Antioxidant testing revealed that the higher the concentration of carrot extract, the greater the antioxidant activity, as indicated by IC50 values of 5.9214 ppm (F1), 3.5381 ppm (F2), and 1.9427 ppm (F3), which are classified as very strong antioxidants. The conclusion of this study is that carrot extract has potential as a source of natural antioxidants in lip balm, with effectiveness increasing with higher extract concentrations. This product can serve as a safe and beneficial natural cosmetic alternative for protecting lips from free radical damage.